(untitled) (Comprehensive Journal of Science, 2026)
Cryptorchidism represents one of the most common congenital anomalies of the male reproductive system in pediatric populations and remains a clinically relevant condition due to its potential long-term consequences. This descriptive study aims to document the histopathological and morphological features of undescended testes in children prior to surgical intervention. Testicular tissue samples were examined using routine histological methods to describe structural characteristics of the seminiferous tubules, germinal epithelium, and interstitial tissue. The observations provide a detailed depiction of pre-treatment tissue features associated with pediatric cryptorchidism. Such descriptive documentation contributes to a clearer understanding of the condition at the tissue level before surgical management.